Military, Politics and Democratization in Southern Africa
XXIX, 278 p. 11 illus., 10 illus. in color.
Keywords: This book explores multiple challenges faced by democratization in Southern Africa. Applying a wider lens to the concept of political transition and employing a variety of theoretical and methodological approaches, the contributions gathered here explore residual political cultural practices that hinder democratic consolidation in Southern Africa. Presenting various case studies, the book tackles themes such as the military-political nexus, leadership renewal, constitutionalism, electoral politics, election violence, marginalization of women, civil society and political transition, media framing and transitional justice. Written from a multidisciplinary perspective and drawing on empirical data from multiple sources, this edited volume challenges orthodox conceptualizations of political transition. The book will be of interest to students and scholars of political science, African studies, and related fields, as well as policy-makers and professionals interested inthe latest political developments in Southern Africa.